Development and evaluation of a new interferon-gamma release assay for the diagnosis of tuberculosis infection in HIV-infected individuals in China. Issue 4 (April 2015) - Yu, Liang; Mo, Pingzheng; Wei, Zeping; Fu, Ruiling; Yang, Mai; Ji, Binying; Wang, Jian; Li, Shu; Strong, Amie J.; Touzjian, Neal; Kushner, Nicholas; Gui, Xi-En; et al.
Abstract: Background: Human immunodeficiency virus (HIV)-infected individuals are at high risk of contracting tuberculosis (TB) disease, and current methods for diagnosing TB infection are less effective in this population. We developed and evaluated a new interferon-gamma release assay (IGRA), named A.TB, in HIV-infected individuals, with and without active TB, in a setting of high TB burden and low HIV prevalence. Methods: A total of 255 subjects were divided into 3 groups according to their HIV and TB status: HIV+ without active TB ( n = 123), HIV+/TB+ ( n = 79), and HIV–/TB+ ( n = 65). The A.TB assay was performed in parallel with the QuantiFERON-TB Gold In-Tube (QFT-GIT) and tuberculin skin test (TST). Results: The positive rate was 59.3% ( n = 123) by A.TB and 53.8% ( n = 106) by QFT-GIT. We observed a strong concordance of 81.2% ( k = 0.612) between the two IGRAs. The QFT-GIT results were affected by low CD4 + cell count ( p = 0.013), while A.TB results were not. A.TB was also performed in patients with active TB ( n = 65) and patients with active TB and HIV co-infection ( n = 79). The sensitivity of A.TB in these groups was 80.0% and 81.0%, respectively. Conclusion: The A.TB results were not affected by low CD4 + cell count in the co-infected cohort. With further evaluation, A.TB may prove to be a valuable tool for diagnosing TB in HIV-infected patients.